Incorporation of groundwater pumping in a global Land Surface Model with the representation of human impacts. Issue 1 (8th January 2015) - Pokhrel, Yadu N.; Koirala, Sujan; Yeh, Pat J.‐F.; Hanasaki, Naota; Longuevergne, Laurent; Kanae, Shinjiro; Oki, Taikan
Abstract: Observations indicate that groundwater levels are declining in many regions around the world. Simulating such depletion of groundwater at the global scale still remains a challenge because most global Land Surface Models (LSMs) lack the physical representation of groundwater dynamics in general and well pumping in particular. Here we present an integrated hydrologic model, which explicitly simulates groundwater dynamics and pumping within a global LSM that also accounts for human activities such as irrigation and reservoir operation. The model is used to simulate global water fluxes and storages with a particular focus on groundwater withdrawal and depletion in the High Plains Aquifer (HPA) and Central Valley Aquifer (CVA). Simulated global groundwater withdrawal and depletion for the year 2000 are 570 and 330 km 3 yr −1, respectively; the depletion agrees better with observations than our previous model result without groundwater representation, but may still contain certain uncertainties and is on the higher side of other estimates. Groundwater withdrawals from the HPA and CVA are ∼22 and ∼9 km 3 yr −1, respectively, which are also consistent with the observations of ∼24 and ∼13 km 3 yr −1 . The model simulates a significant decline in total terrestrial water storage in both regions as caused mainly by groundwater storage depletion. Groundwater table declined by ∼14 cm yr −1 in the HPA during 2003–2010; the rate is even higher (∼71 cm yr −1 ) in the CVA. These results demonstrate the potential of the developed model to study the dynamic relationship between human water use, groundwater storage, and the entire hydrologic cycle. Key Points: Global Land Surface Model with human impacts, groundwater dynamics, and pumping Explicitly simulated groundwater withdrawal and depletion Groundwater depletion in the Central Valley and the High Plains